Retraction Notice - Edwin Cock, Ian (Asian Journal of Biological and Life Sciences)
A Sydney research group recently reported that compounds found in elderberries (Sambucus spp.; Figure 2) can directly inhibit the entry of influenza virus into human cells. Specifically, the compound blocks key viral proteins that are vital for both viral attachment and cell entry. Furthermore, the study published in the Journal of Functional Foods1 also determined that the compound inhibited viral replication within the cell. The ability of the elderberry compound to block the viral life cycle is interesting as this provides it with greater antiviral efficacy. Of further note, other compounds in the elderberry extract stimulatecytokine release, thereby stimulating the immune system and providing a coordinated response should the virus evade the cell entry and replication inhibitor activities of the elderberry extracts.